2008
DOI: 10.1007/s10695-008-9219-0
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms underlying sex change in hermaphroditic groupers

Abstract: Groupers are widely distributed throughout the tropical and subtropical waters of the world and are regarded as a favourite marine food fish. However, their large-scale aquaculture has been hindered by the rarity of natural males. Being protogynous hermaphrodites, groupers have been considered as study model for development and reproduction, especially for sex determination or sex differentiation, owing to the advantage that grouper gonad development undergoes transition from ovary to intersexual gonad and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
43
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 72 publications
(47 citation statements)
references
References 85 publications
4
43
0
Order By: Relevance
“…Actually, several important genes, such as Fushi Tarazu factor-1 (FTZ-F1), Sry-related HMG-box gene 9 (SOX9), Wilms tumor gene 1 (WT1), anti-mullerian hormone (AMH), DMRT1 and the zinc finger transcription factor GATA binding proteins 4 (GATA4), have been supposed as candidate sex determination genes, and a hypothetical regulation hierarchy for sex determination and differentiation has been suggested in the hermaphroditic groupers [86]. In mammals, primary sex determination genes have been divided into 4 classes, in which class I comprises Y genes that have a male-specific effect required for spermatogenesis, class II are X genes that are expressed at a higher level in females than in males by virtue of the 2:1 ratio, class III are X genes that receive a parental imprint, and class IV are sex-specific regions of heterochromatin that exert effects on the epigenetic status of the rest of the genome [87].…”
Section: Sex Determination and Candidate Sex Determination Genesmentioning
confidence: 99%
“…Actually, several important genes, such as Fushi Tarazu factor-1 (FTZ-F1), Sry-related HMG-box gene 9 (SOX9), Wilms tumor gene 1 (WT1), anti-mullerian hormone (AMH), DMRT1 and the zinc finger transcription factor GATA binding proteins 4 (GATA4), have been supposed as candidate sex determination genes, and a hypothetical regulation hierarchy for sex determination and differentiation has been suggested in the hermaphroditic groupers [86]. In mammals, primary sex determination genes have been divided into 4 classes, in which class I comprises Y genes that have a male-specific effect required for spermatogenesis, class II are X genes that are expressed at a higher level in females than in males by virtue of the 2:1 ratio, class III are X genes that receive a parental imprint, and class IV are sex-specific regions of heterochromatin that exert effects on the epigenetic status of the rest of the genome [87].…”
Section: Sex Determination and Candidate Sex Determination Genesmentioning
confidence: 99%
“…RT-PCR analysis of RGV-infected RGS cells showed that RGV could replicate in RGS cells. Further study of virus replications in RGS cells was conducted by electron microscopy and immunofluorescence microscopy has shown that virus particles Introduction Groupers, which are widely distributed throughout the tropical and subtropical waters of the world, are economically important marine fish and ideal study models for development and reproduction (Zhou et al 2007;Zhou and Gui 2010). Due to the development of intensive aquaculture industry in recent years, infectious diseases caused by viruses, bacteria, and parasites have become major constraints in grouper farming, of which viruses are the most devastating and most widely reported infectious agents for cultured groupers (Chi et al 1999;Lai et al 2003;Xu et al 2010).…”
mentioning
confidence: 99%
“…Increasing evidences have indicated that most of the known sex determination genes discovered so far in vertebrates are derived from the duplicated homologs of Dmrt1 gene (Chong et al, 2013;Gamble and Zarkower, 2012;Gempe and Beye, 2011;Graves, 2013;Herpin and Schartl, 2011;Kikuchi and Hamaguchi, 2013;Matson and Zarkower, 2012;Siegal and Baker, 2005;Zhou and Gui, 2010). For gibel carp, as a unisexual lineage that is able to utilize gynogenesis as a unisexual reproduction mode, how male individuals arise and how male determination genes evolve will be the merit for further investigation.…”
Section: Discussionmentioning
confidence: 99%